2003
DOI: 10.1002/mmce.10120
|View full text |Cite
|
Sign up to set email alerts
|

Systematic and efficient root finder for computing the modal spectrum of planar layered waveguides

Abstract: An efficient and systematic strategy to find the propagation constants of real, complex, and leaky modes of covered and uncovered planar multilayered isotropic/uniaxial waveguides is presented. This strategy first builds up a pole-free characteristic function and then makes use of a root-searching scheme based on an integral nature method to search for its zeros. For uncovered waveguides, the branch points of the characteristic function can be removed by introducing the upper half-space vertical wavenumber as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…The values of these poles and residues have been computed for the particular spectral-domain Green's function of Fig. 6 by means of an appropriate numerical algorithm [44], and the results are shown in Table I Table I(B) within six significant figures. The real part of the residues at the aforementioned poles also coincide within four significant figures.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of these poles and residues have been computed for the particular spectral-domain Green's function of Fig. 6 by means of an appropriate numerical algorithm [44], and the results are shown in Table I Table I(B) within six significant figures. The real part of the residues at the aforementioned poles also coincide within four significant figures.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Looking at (28), (29), (32), (33), (36), and (37), it can be observed that the functions denoted in this paper by (i.e., , and ) are all linear combinations of functions of the type (44) where…”
Section: Appendixmentioning
confidence: 98%
“…Recently, the method based on the Cauchy integral has become more popular to solve these sets of equations [11,12]. It has the property that is valid for any complex transcendental equation, and additionally it needs no previous information or seed.…”
Section: Introductionmentioning
confidence: 99%
“…It has been employed more recently on planar circuits by Y. Long [15][16][17], for microstrip lines by Mesa et al [11], for microstrip antennas [18], and also for circular-waveguide resolution [19].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it does not need any previous information or seed. The method has been employed recently on planar circuits [10][11][12], for microstrip lines [13], for microstrip antennae [14], and also for the rectangular [15] and circular [16] waveguides resolution.…”
Section: Introductionmentioning
confidence: 99%